Regulation of the Higher-Order Structure of Chromatin by Histones H1 and H5 - Allan, James; Cowling, Graham J.; Harborne, Nerina; Cattini, Peter; Craigie, Robert; Gould, Hannah (The Journal of cell biology, 1981)
Chicken erythrocyte chromatins containing a single species of linker histone, H1 or H5, have been prepared, using reassembly techniques developed previously. The reconstituted complexes possess the conformation of native chicken erythrocyte chromatin, as judged by chemical and structural criteria; saturation is reached when two molecules of linker histone are bound per nucleosome, as in native erythrocyte chromatin, which the resulting material resembles in its appearance in the electron microscope and quantitatively in its linear condensation factor relative to free DNA. The periodicity of micrococcal nuclease-sensitive sites in the linker regions associated with histone H1 or H5 is 10.4 base pairs, suggesting that the spatial organization of the linker region in the higher-order structure of chromatin is similar to that in isolated nucleosomes. The susceptible sites are cut at differing frequencies, as previously found for the nucleosome cores, leading to a characteristic distribution of intensities in the digests. The scission frequency of sites in the linker DNA depends additionally on the identity of the linker histone, suggesting that the higher-order structure is subject to secondary modulation by the associated histones.